Evaluation of efficacy and safety of robotic stereotactic body radiosurgery and hypofractionated stereotactic radiotherapy for vertebral metastases - Księżniak-Baran, Dorota; Blamek, Sławomir; Roch-Zniszczoł, Agata; Stąpór-Fudzińska, Małgorzata; Miszczyk, Leszek (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study: The purpose of this study was to evaluate the efficacy and safety of applying CyberKnife (CK) radiosurgery in patients with spinal metastases. Material and methods: Twenty-eight patients with vertebral metastases treated using the CK system were included in the study. Eleven patients suffered from pain, and in 1 case neurological symptoms were observed. The remaining patients were free from clinical symptoms of metastatic disease. The doses applied ranged between 8 and 40 Gy delivered in 4 fractions of 8–15 Gy. Results: In the first follow-up evaluation (mean 4.5 months after the treatment), pain was stable in 5 of 8 evaluable cases and in 3 regression occurred. The last follow-up examination (mean 11 months after stereotactic radiosurgery) revealed stable ailments in 3 of 6 evaluable cases, improvement in 3 and new complaints in another 4 patients. In 17 patients imaging studies were conducted after a mean time of 11 months after CK treatment. Stabilization was confirmed in 11, regression in 4 and progression in 2 cases. Median overall survival was 20.6 months. Median progression-free survival was 12.6 months. No side effects attributable to the treatment were observed, but during follow-up transient or permanent deterioration in neurological status as a consequence of disease progression was diagnosed in 4 patients. Delivery time of a single fraction ranged between 0.5 and 1.5 hours. Conclusions : Robotic stereotactic radiosurgery as part of multimodality therapy for metastatic spinal tumours is safe and effective. Because of long irradiation times, this kind of treatment is not suitable for patients in poor general condition.